Birds of a feather flock together: ownership in cross-border acquisitions by emerging multinationals. Issue 1 (22nd September 2020) - Domínguez, Beatriz; Fuentelsaz, Lucio; Garrido, Elisabet; González, Minerva
Abstract : Purpose: Despite prior studies on cross-border acquisitions (CBAs) have analyzed the determinants of ownership strategies; there is still a quest for evidence on how the differences between home and host market characteristics affect the ownership percentage. Prior studies have acknowledged that entering host countries with greater uncertainty makes multinationals reluctant to acquire high levels of ownership. Nevertheless, emerging multinationals (EMNEs) are usually used to operating under greater levels of uncertainty than multinationals from advanced countries (AMNEs), which can imply different ownership strategies. The purpose of this study is to analyze the ownership percentage acquired by MNEs when designing a CBA in emerging or in advanced countries, and to analyze the extent to which the ownership strategy in emerging countries differs between EMNEs and AMNEs. Design/methodology/approach: Mobile telecommunications industry is used as research setting to provide empirical evidence of the interaction effect of the advanced versus emerging nature of the host and home countries on the ownership acquired in CBAs. Findings: Results confirm that both home and host countries' characteristics are relevant in explaining the ownership strategies of MNEs. Originality/value: The authors contribute to the strategy and IB literatures by providing empirical evidence on the recent debate on whether the internationalization strategies followed by EMNEs are similar to the traditional patterns of AMNEs, and analyze how EMNEs differ from AMNEs in their ownership strategies in emerging countries. Focusing in the mobile telecommunications industry, the authors also contribute by extending the analysis to an international and cross-cultural setting that includes 48 mobile groups that come from 35 home and 81 host countries.